Attachment of HeT-A Sequences to Chromosomal Termini in Drosophila melanogaster May Occur by Different Mechanisms - Kahn, Tatyana (American Society for Microbiology, 2000)
Drosophila telomeres contain arrays of the retrotransposonlike elements HeT-A and TART. Their transposition to broken chromosomal termini has been implicated in chromosome healing and telomere elongation. The HeT-A element is attached by its 3′ end, which contains the promoter. To monitor the behavior of HeT-A elements, we used the yellow gene with terminal deficiencies consisting of breaks in the yellow promoter region that result in the y-null phenotype. Attachment of the HeT-A element provides the promoterless yellow gene with a promoter that activates yellow expression in bristles. The frequency of HeT-A transpositions to the yellow terminal deficiency depends on the genotype of the line and varies from 2 × 10(−3) to less than 2 × 10(−5). Loss of the attached HeT-A due to incomplete replication at the telomere leads to inactivation of yellow expression, which is restored by attachment of a new HeT-A element upstream of yellow. New HeT-A additions occur at a frequency of about 1.2 × 10(−3). Short DNA attachments are generated by gene conversion using the homologous telomeric sequences as templates. Longer DNA attachments are generated either by conventional transposition of an HeT-A element to the chromosomal terminus or by recombination between the 3′ terminus of telomeric HeT-A elements and the receding end of HeT-A attached to the yellow gene.